Protection of Cattle Elicited Using a Bivalent Lumpy Skin Disease Virus-Vectored Recombinant Rift Valley Fever Vaccine - Wallace, David B.; Mather, A.; Kara, P. D.; Naicker, Leeann; Mokoena, Nobalanda B.; Pretorius, A.; Nefefe, T.; Thema, N.; Babiuk, Shawn (Frontiers in Veterinary Science, 2020)
Lumpy skin disease and Rift Valley fever are two high-priority livestock diseases which have the potential to spread into previously free regions through animal movement and/or vectors, as well as intentional release by bioterrorists. Since the distribution range of both diseases is similar in Africa it makes sense to use a bivalent vaccine to control them. This may lead to the more consistent and sustainable use of vaccination against Rift Valley fever through a more cost-effective vaccine. In this study, a recombinant lumpy skin disease virus was constructed in which the thymidine kinase gene was used as the insertion site for the Gn and Gc protective glycoprotein genes of Rift Valley fever virus using homologous recombination. Selection markers, the enhanced green fluorescent protein and Escherichia coli guanidine phosphoribosyl transferase (gpt), were used for selection of recombinant virus and designed to allow for a second recombination event to occur upon removal of the gpt selection-pressure allowing the removal of both marker genes in the final product. This recombinant virus, LSD-RVF.mf, was selected to homogeneity, characterised and evaluated in cattle as a vaccine to show protection against both lumpy skin disease and Rift Valley fever in cattle.